Rediscovering the Relevance of Boenninghausen and Bogerʼs Concepts – Part I - Thakar, Munjal (Homœopathic Links, 2012)
This article discusses a retrospective analysis of some of the actual cases from Boenninghausenʼs practice. Cases were solved to see a pattern in which he did the case taking, erected a portrait and ultimately arrived at a remedy. This brings a real-time insight into the concepts and the thought process of this great mind. The literature reading was done only after the analysis from the cases was concluded; therefore it was more with an intention to confirm the findings of the author. Besides, this approach made up for the gaps, if any, between the practiced and the written.
Keywords: Boenninghausen; Characteristics; Portrait; Concomitants; Complete symptom; Generalization; Form-pattern